The natural step for communities : how cities and towns can change to sustainable practices - James, Sarah (New Society Publishers, 2004)
This book provides examples of communities that have made dramatic changes toward sustainability, and explains how others can emulate their success. Arguing that the process of introducing change--whether converting to renewable energy or designing compact development--is critical to success, the authors outline why well-intentioned proposals often fail to win community approval, and why an integrated approach--not "single-issue" initiatives--can surmount challenges of conflicting priorities, scarce resources, and turf battles. Key to success is a democratic "bottom-up" change process, and clear guiding sustainability principles such as the Natural Step framework.--From publisher description.